INSPECTING THE PROFESSION OF GOVERNMENT ACCOUNTANTS IN THE FUTURE - Puji Wibowo; Amrie Firmansyah (AFEBI Accounting Review, 2018)
The accountant has become one of the most prestigious professions around the world since a few decades ago. Research concerning accountant professions has simultaneously been famous and even abundant since then. A number of existing studies discussed these fabulous professions, namely public accountant and chartered accountant, from college students’ point of views. This research offers a new perspective with respect to the type of professions and group of respondents. By undertaking questionnaire survey and interviews with government officers as selected respondents, this study tries to reveal the public officers' perceptions, instead of students, towards accountancy professions in the line ministries and government agencies. The questionnaires were distributed to government employees whose jobs are related to public finance management amounted to 300 questionnaires in total. 104 questionnaires were successfully returned, and from those 97 are valid. This preliminary study focuses on government officers’ attitude because this topic has been unusual. The study becomes more challenging since it also discusses the impact of Ministry of Finance Decree No. 25 of 2014 concerning State Chartered Accountant on the willingness of government officers to choose professional accountant in public sector as an option to pursue their career. We find that respondents agree with the obligation of re-register of chartered accountant and the role of Indonesian Accountant Association in the process of registration. However, respondents who have already been registered in National Chartered Accountants were not sure whether they would be able to undertake continuous learning program until the retirement ages. This study also discloses that most respondents tend to say that in upcoming years, government accountants have more important roles in audit, taxation, education, local government finance, national budget, cost of public services, and non-tax revenue. Finally, this research proposes policy recommendation that government should take professional accountants into account in arranging career path for public officers. Keywords: chartered accountant, government officers